Penafsiran Para Mufasir Pada Ayat-Ayat Trinitas - Fuad, Khairul; Kerwanto, Kerwanto; Nurbaiti, Nurbaiti (Jurnal Global Ilmiah, 2025)
The majority of scholars agree that these three verses are verses that express the belief in the three Gods in Christianity, both the Trinity and Tritheism. In explaining these verses, the mufasir often mention sects in Christianity, such as Ya'qubiyah, Mulkiyah, Nasturiyah, and others. In the Christian confession, Mary is only the Mother of Jesus, and is not considered God. Christians inform that what they believe is the Holy Spirit. Maryam is one of God's persons. However, the mufasir are very convinced that Mary is one of the formulations of the Trinity, not the Holy Spirit. As mentioned by the majority of mufasir, there is a sect called Collydrians who believe in Mary as God. The author proves that the sect once existed. In this study, the author used a qualitative method. The data was obtained through library research using classical and contemporary interpretations and sources of Christian literature. In this paper, various historical issues will be contained, including the dialogue between the Qur'an and Christianity, as well as the debate between Islam and Christianity on the verses of the Trinity.